The interwoven nature of spatial presence and virtual embodiment: a comprehensive perspective - Halbig, Andreas; Latoschik, Marc Erich (Frontiers in Virtual Reality, 2025)
The sense of embodiment and the sense of spatial presence are two fundamental constructs in Virtual Reality, shaping user experience and behavior. While empirical studies have consistently shown that both constructs are influenced by similar cues, theoretical discussions often treat them as separate, leaving their conceptual relationship underexplored. This paper systematically examines the conceptual overlap between these two constructs, revealing the extent of their interconnection. Through a detailed analysis, we present fourteen arguments that demonstrate how cues designed to enhance one construct also impact the other. This unified perspective highlights that any cue contributing to one construct is likely to influence the other. Furthermore, our findings challenge the suitability of common network-based models in representing the relationship between the two constructs. As an alternative, we suggest a table-based representation that maps the influence of individual cues onto both constructs, highlighting their relative impact. By bridging this theoretical gap, our work clarifies the intertwined nature of these constructs, with potential applications in the development of more cohesive measurement instruments and further research in presence and embodiment.